Gambling, saving, and lumpy liquidity needs - Herskowitz, Sylvan (American Economic Association, 2021)
I present evidence that unmet liquidity needs for indivisible, “lumpy,” expenditures increase demand for betting as a second-best method of liquidity generation in the presence of financial constraints. With a sample of 1,708 sports bettors in Kampala, Uganda, I show that participants’ targeted payouts are linked to anticipated expenditures, while winnings increase lumpy expenditures disproportionately. I show that a randomized savings treatment decreases demand for betting. And I use two lab-in-the-field experiments to show that unmet liquidity needs and saving ability are important mechanisms. These results cannot be explained by betting as a purely normal good. (JEL C93, D81, G51, L83, O12, O16)